2018
DOI: 10.1111/nyas.13866
|View full text |Cite
|
Sign up to set email alerts
|

Sm‐p80‐based vaccine trial in baboons: efficacy when mimicking natural conditions of chronic disease, praziquantel therapy, immunization, and Schistosoma mansoni re‐encounter

Abstract: Sm-p80-based vaccine efficacy for Schistosoma mansoni was evaluated in a baboon model of infection and disease. The study was designed to replicate a human vaccine implementation scenario for endemic regions in which vaccine would be administered following drug treatment of infected individuals. In our study, the Sm-p80-based vaccine reduced principal pathology producing hepatic egg burdens by 38.0% and egg load in small and large intestines by 72.2% and 49.4%, respectively, in baboons. Notably, hatching rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
0
27
0
1
Order By: Relevance
“…14,15 To develop a viable schistosomiasis vaccine, the efficacy of an Sm-p80-based vaccine was systematically evaluated in baboons (Papio anubis), natural hosts of schistosomiasis and the most relevant nonhuman primate model of human clinical man-ifestations of both acute and chronic disease. [16][17][18] Sm-p80 is the heavy chain of the S. mansoni calcium activated neutral protease (calpain), and is the only classical calpain among the nonhuman calpains. 19,20 Sm-p80 meets the requirements for a suitable schistosome vaccine candidate because it is present in the surface membranes and epithelial syncytium of the worm, 21,22 it is one of the immunodominant membrane antigens, 22 and it displays no immunological cross-reactivity with human or other vertebrate calpains.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 To develop a viable schistosomiasis vaccine, the efficacy of an Sm-p80-based vaccine was systematically evaluated in baboons (Papio anubis), natural hosts of schistosomiasis and the most relevant nonhuman primate model of human clinical man-ifestations of both acute and chronic disease. [16][17][18] Sm-p80 is the heavy chain of the S. mansoni calcium activated neutral protease (calpain), and is the only classical calpain among the nonhuman calpains. 19,20 Sm-p80 meets the requirements for a suitable schistosome vaccine candidate because it is present in the surface membranes and epithelial syncytium of the worm, 21,22 it is one of the immunodominant membrane antigens, 22 and it displays no immunological cross-reactivity with human or other vertebrate calpains.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported a significant reduction in hatching rates of eggs excreted in feces [48]. In another recent study designed to mimic field scenario of schistosomiasis vaccine deployment, it was shown that Sm-p80-based vaccination following PZQ treatment of chronically-infected baboons caused a significant reduction in tissue egg retention and hatching rates when subsequently challenged with S. mansoni cercariae [49]. Notably, infected human populations tested to date have not been shown to express Sm-p80-specific IgE antibodies [50,51] thereby lessening the potential risk of severe allergic reaction.…”
Section: Schistosoma Mansoni Calpainmentioning
confidence: 92%
“…Immunization of an individual is likely to be achieved with multiple vaccine doses spread across a number of weeks [14], dependent on vaccine characteristics and logistical factors. Given this uncertainty, we made the simplifying assumption that immunization occurs instantaneously at a specified time point.…”
Section: Methodsmentioning
confidence: 99%
“…In keeping with recent trials of Sm-p80 vaccines in baboons, we made three key assumptions about the vaccine [14]. We assumed the vaccine does not have a therapeutic effect on already established schistosomes, i.e.…”
Section: Methodsmentioning
confidence: 99%